Emotional concerns and coping strategies in Low Grade Glioma patients and reliability of their caregivers in reporting these concerns: Findings from a cross-sectional study. (October 2017) - Moreale, Renzo; Campanella, Fabio; Marin, Francesca; Skrap, Miran; Palese, Alvisa
Abstract: Purpose: To explore the emotional concerns and coping strategies of patients with Low Grade Glioma (LGG) and whether or not their caregivers are reliable in reporting these concerns as surrogate informants. Methods: An explorative cross-sectional study. Patients who had undergone a neurosurgical procedure at least one year before this study for LGG and who were capable of participating in a face-to-face interview were included. Each patient nominated a reference caregiver. Both the patient and the caregiver were interviewed independently, using the Beck Depression Inventory Scale, the State – Trait Anxiety Inventory, and the Jalowiec Coping Scale. Main results: Forty-six patients and 46 caregivers were included. The average scores of the Beck scale were homogeneous between patients and caregivers (7.76 [CI 95% 5.76–9.75] vs. 6.23 [CI 95% 4.57–7.90]; p = 0.102). Patients reported significantly greater state and trait anxiety (44.26 [CI 95% 40.21–48.31] and 37.95 [CI 95% 34.97–40.94]), respectively compared to their caregivers (40.28 [CI 95% 36.64–43.91] and 35.17 [CI 95% 32.16–38.18]). The coping strategies enacted were homogeneous between patients and caregivers (82.78 [CI 95% 77.21–88.35] vs (80.93 [CI 95% 76.32–85.55]; p = 0.102) while the kind of strategies adopted were significantly diverse. Conclusions: Patients suffer from depression and greater state anxiety as compared to trait anxiety; moreover, they enact less than half of the available coping strategies. Caregivers may be involved as surrogate informants when necessary for health-care professionals to detect depression while more caution is advised for what concerns anxiety and the coping strategies enacted by patients. Highlights: Patients with LGG in their post-operative period suffer from depression and from greater state anxiety as compared to trait anxiety; aiming to deal with this challenging situation, they use less than half of the coping strategies available. Caregivers' perceptions are considered important and may support health-care professionals in tailoring interventions. Caregivers have a reliable perception of the depressive state experienced by the patient; differently, they perceive lower scores of anxieties and different kind of coping strategies as compared to those used by their beloved.